Applying the Chicago Classification criteria of esophageal motility to a pediatric cohort: effects of patient age and size. Issue 9 (23rd July 2014) - Singendonk, M. M. J.; Kritas, S.; Cock, C.; Ferris, L.; McCall, L.; Rommel, N.; van Wijk, M. P.; Benninga, M. A.; Moore, D.; Omari, T. I.
Abstract Background Applying the 2012 Chicago Classification (CC) of esophageal motility disorders to pediatric patients is problematic as it relies upon adult‐derived criteria. As shorter esophageal length and smaller esophago‐gastric junction (EGJ) diameter may influence CC metrics, we explored the potential for age‐ and size‐adjustment of diagnostic criteria. Methods We evaluated 76 high‐resolution solid state impedance‐manometry recordings in children referred for manometry (32M; mean age 9 ± 1 years) and 25 recordings from healthy adult subjects (7M; mean age 36 ± 2 years). CC metrics; integrated relaxation pressure (IRP4s, mmHg), contractile front velocity (CFV, cm/s), distal contractile integral (DCI, mmHg cm/s), distal latency (DL, s), and peristaltic break size (BS, cm) were derived for 10 liquid swallows using CC analysis software. Effects of age and size were examined using regression analysis. Key Results Younger patient age and shorter size correlated significantly with greater IRP4s (p < 0.05), shorter DL (p < 0.001) and smaller BS (p < 0.05). Standard diagnostic CC criteria were adjusted using the slope of the linear regression equation to define the age/size‐related trend. Sixty‐six percent of the pediatric cohort showed abnormal motility when applying standard CC criteria. Adjustment for age and size reduced this to 50% and 53% respectively, with the largest reduction being in the IRP4s‐ and DL‐dependent disorders EGJ outflow obstruction and diffuse esophageal spasm (13% to 7% and 5% and 14% to 1 and 5%, respectively). Conclusions & Inferences CC metrics, particularly IRP4s and DL, are age and size dependent, and therefore, require adjustment to improve accuracy of diagnosis of esophageal motility disorders in children.